Dinamika Peran Gerakan Sosial Keagamaan NU Dalam Merespon Perubahan Sosial - Saepulah (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI Miftahul Huda Subang, 2022)
In Indonesia, Nahdatul Ulama (NU) is one of the largest Islamic organizations. As a mass-based organization, NU is unique. It is not the same as other Islamic organizations. Its uniquness can be seen from the dynamics of NU‟s role in dealing with the socio-political changes that have occurred in Indonesia. NU sometimes has a defensive, opportunistic, and sometimes even a radical. This dynamic characteristic of NU will be read from a social movement perspective. This article utilizes library research method with NU as a case study. The data that has been collected is then described and analyzed. Having used Smelser‟s theory of “collective behavior”, this article concludes that the dynamics of NU‟s role in responding to changes in the socio-political constellation in Indonesia are a result of structural constraints, supporting factors, generalized beliefs, mobilization, and the existence of intellectual actors.